Epigenomics in Hurthle Cell Neoplasms: Filling in the Gaps Towards Clinical Application - Canberk, Sule; Lima, Ana Rita; Pinto, Mafalda; Soares, Paula; Máximo, Valdemar (Frontiers in Endocrinology, 2021)
It has been widely described that cancer genomes have frequent alterations to the epigenome, including epigenetic silencing of various tumor suppressor genes with functions in almost all cancer-relevant signalling pathways, such as apoptosis, cell proliferation, cell migration and DNA repair. Epigenetic alterations comprise DNA methylation, histone modification, and microRNAs dysregulated expression and they play a significant role in the differentiation and proliferation properties of TC. In this review, our group assessed the published evidence on the tumorigenic role of epigenomics in Hurthle cell neoplasms (HCN), highlighting the yet limited, heteregeneous and non-validated data preventing its current use in clinical practice, despite the well developed assessment techniques available. The identified evidence gaps call for a joint endeavour by the medical community towards a deeper and more systematic study of HCN, aiming at defining epigenetic markers in early diagnose, allowing for accurate stratification of maligancy and disease risk and for effective systemic treatment.